2009
DOI: 10.1017/s0007114509992431
|View full text |Cite
|
Sign up to set email alerts
|

The effect of polyphenol-rich dark chocolate on fasting capillary whole blood glucose, total cholesterol, blood pressure and glucocorticoids in healthy overweight and obese subjects

Abstract: Numerous studies indicate that polyphenol-rich chocolate reduces fasting blood glucose, blood pressure (BP) and total cholesterol in healthy individuals and hypertensives with or without glucose intolerance. The aim of the present study was to investigate the effect of two doses of polyphenol-rich dark chocolate (DC) on fasting capillary whole blood glucose, total cholesterol and BP and to examine whether improvements in these parameters are associated with changes in adrenocorticoid excretion in overweight an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 64 publications
6
65
1
Order By: Relevance
“…The improvements were observed in both groups, indicating that cocoa supplementation did not have additional effect on those variables and attributing the observed changes to the hypocaloric diet followed by the volunteers. Our results are in agreement with two previous studies and one meta-analysis, in which no changes were observed in body size and composition of overweight/obese subjects after the cocoa supplementation (9,16,17). Golomb et al observed a negative correlation between the frequency of dark chocolate consumption and BMI (18).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The improvements were observed in both groups, indicating that cocoa supplementation did not have additional effect on those variables and attributing the observed changes to the hypocaloric diet followed by the volunteers. Our results are in agreement with two previous studies and one meta-analysis, in which no changes were observed in body size and composition of overweight/obese subjects after the cocoa supplementation (9,16,17). Golomb et al observed a negative correlation between the frequency of dark chocolate consumption and BMI (18).…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have observed a strong link between their consumption and a decrease of blood pressure (BP) levels (9). Moreover, cocoa flavanols can influence blood lipid levels by decreasing lowdensity lipoprotein-cholesterol (LDL-c), increasing high-density lipoprotein-cholesterol (HDL-c) and inhibiting oxidized LDL-c production (oxLDL), which is one of the most important triggers implicated in atherosclerosis (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Cocoa’s effects on insulin resistance may be dependent on its continual consumption over a longer period of time. Two studies have indicated improvements within two weeks of insulin-mediated vasodilation (through increased NOS levels) and fasting capillary whole blood glucose, but the two week trial period did not demonstrate improved measures of insulin resistance [20,25]. …”
Section: Positive Effectsmentioning
confidence: 99%
“…This is due to the action of flavan-3-ols which augment endothelial NOS and thereby enhance the production of nitric oxide (NO), thereby improving endothelium-dependant vasorelaxation [95]. Cacao decreases blood pressure [96,97], increases insulin sensitivity [96], increases HDL cholesterol concentrations [98] and reduces blood platelet stickiness and clotting [91,92].…”
Section: Cacaomentioning
confidence: 99%